Evolutionary Trajectory of Hindutva in Nepal and India - Lawoju, Niraj (Bagiswori Journal, 2025)
Hindutva, as a Hindu nationalist political theory has major impact on the South Asian polity. History of Hindutva traces back to the Indian struggle of independence. Nevertheless, recently Hindutva became much impactful, particularly since 2014 after BJP, one of the major Hindutva political parties re-emerged into Indian central political power. Nepal has obvious impact of this political change in India, not only because Nepal is one of the neighboring countries of India, also because Nepal is a Hindu-majority country and once a Hindu nation. Hindutva ideologues have always described Nepal as a model Hindu nation also to consolidate their objective to establish India as a Hindu nation. Interestingly, when Hindutva ideology is at the central stage of Indian politics, Nepal no longer is a Hindu nation. Evolution of Hindutva politics has different trajectory in Nepali context. This paper studies how Hindutva politics historically evolved in Nepal and shows how it differs from Indian context notwithstanding fundamental similarities. Indian ideologues had developed Hindutva as a political theory but it was already in practice in Nepal in different ways long before it took a shape of a political theory. This research makes academic enquiry of historical documents and research papers as data sources to analyze the evolutionary trajectory of the Hindutva in Nepal against the backdrop of Hindutva theory evolved in India.